2022
DOI: 10.4103/jfmpc.jfmpc_973_21
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of hypertension and cardiovascular diseases in patients recovered from COVID-19: An Indian perspective

Abstract: Objective: The aim of this study was to understand the prevalence, extent, clinical approach of hypertension and cardiovascular disease (CVD) in patients recovered from COVID-19. Methods: The round table meetings (RTMs) and survey convened a diverse panel of specialists including cardiologists, endocrinologists, diabetologists, consultant physicians, and family physicians from various geographical zones of India. A standard questionnaire including 10 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Among COVID-19 patients, there is an increased susceptibility to developing venous thromboembolism and arterial thrombotic events, which can subsequently manifest as strokes, heart attacks, or pulmonary embolisms. Additionally, some COVID-19 patients experience exacerbations of preexisting hypertension or the onset of new hypertension, along with the observation of arrhythmias such as atrial fibrillation (Tudoran et al, 2022;Re et al, 2022;Krishnakumar et al, 2022).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Among COVID-19 patients, there is an increased susceptibility to developing venous thromboembolism and arterial thrombotic events, which can subsequently manifest as strokes, heart attacks, or pulmonary embolisms. Additionally, some COVID-19 patients experience exacerbations of preexisting hypertension or the onset of new hypertension, along with the observation of arrhythmias such as atrial fibrillation (Tudoran et al, 2022;Re et al, 2022;Krishnakumar et al, 2022).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Research has also revealed the likelihood of post-acute sequelae in some COVID-19 survivors, including chronic myocarditis and cardiomyopathies. COVID-19 has a complex effect on the cardiovascular system, covering direct viral impacts, inflammatory processes, endothelial dysfunction, and thrombotic tendencies (Krishnakumar et al, 2022;Elseidy et al, 2022;Santoro et al, 2023).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Исследование, в котором приняли участие 3066 врачей первичного звена Индии, выявило, что до 20% выздоровевших от COVID-19 пациентов имеют неконтролируемую гипертензию [43]. Почти 52% медицинских работников для контроля АД у пациентов с АГ, перенесших COVID-19, перешли с монотерапии на двойную комбинацию, 20% увеличили дозу двойной терапии и 13% использовали тройную терапию [43].…”
Section: аг и постковидный синдромunclassified
“…COVID-19 exerts a significant impact on the cardiovascular system, giving rise to complications like acute coronary syndrome, myocardial infarction, fluctuations in blood pressure, and the exacerbation of pre-existing cardiovascular diseases. 251 Studies consistently highlight that hypertension and cardiovascular diseases are the most prevalent co-existing conditions in individuals afflicted with COVID-19. 252,253 The association likely involves the dysregulation of the RAAS and ACE2 system, along with the strain caused by acute lung injury, which increases the workload on the heart.…”
Section: Hypertension and Corona Virus-19 (Co-vid-19)mentioning
confidence: 99%